Some Spectra of Superposition Operators Generated by an Exponential Function - Halilović, Sanela (Communications in Mathematics and Applications, 2021)
In the present paper we consider the nonlinear superposition operator \(F\) in Banach spaces of sequences \(l_p\) \((1p∞)\), generated by the function \(f(s, u) = d(s) + a^ku - 1\), with \(a > 1\) and \(kR{0}\). We find out the Rhodius spectra \(σ_R(F)\) and the Neuberger spectra \(σ_N(F)\) of these operators, depending on the values of \(k\).